Shana’s Story: The Struggles, Quandaries and Pitfalls Surrounding Self-determination - Petersen, Amy J. (Disability Studies Quarterly, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>This qualitative research study explores the concept of self-determination as experienced by an African American woman labeled with a disability in an educational setting. When articulated as a particular set of skills to be acquired, this study found that the democratic intent of self-determination was undermined. In this case, self-determination became the antithesis of the movement's intent, instead resembling a process of normalization. Employing poetry to illuminate the participant’s experiences, this research draws attention to the quandaries that arise when self-determination is enacted via a technical-rational instructional paradigm.